2020
DOI: 10.1136/bmj.m4677
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of clinical manifestations and risk of death in patients admitted to hospital with covid-19 and seasonal influenza: cohort study

Abstract: OBJECTIVE To comparatively examine differences in risk of clinical manifestations and death among people admitted to hospital with coronavirus disease 2019 (covid-19) and seasonal influenza. DESIGN Cohort study. SETTING US Department of Veterans Affairs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
164
4
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 159 publications
(187 citation statements)
references
References 44 publications
13
164
4
6
Order By: Relevance
“…Another remarkable observation is that patients with SARS-CoV-2 infection were significantly younger than those with seasonal influenza. The median age of COVID-19 patients in our study was lower than in recent multi-center cohort studies of patients hospitalized with SARS-CoV-2 infection in Germany that observed a mean age of 68-70 years 36,37 and with a recent cohort study analyzing electronic healthcare databases of the US Department of Veterans Affairs that observed a mean age of 69 years 19 . However, our observation that patients with SARS-CoV-2 infection are generally younger than seasonal influenza patients is consistent with previously published data 14,15,18 .…”
Section: Discussioncontrasting
confidence: 82%
See 3 more Smart Citations
“…Another remarkable observation is that patients with SARS-CoV-2 infection were significantly younger than those with seasonal influenza. The median age of COVID-19 patients in our study was lower than in recent multi-center cohort studies of patients hospitalized with SARS-CoV-2 infection in Germany that observed a mean age of 68-70 years 36,37 and with a recent cohort study analyzing electronic healthcare databases of the US Department of Veterans Affairs that observed a mean age of 69 years 19 . However, our observation that patients with SARS-CoV-2 infection are generally younger than seasonal influenza patients is consistent with previously published data 14,15,18 .…”
Section: Discussioncontrasting
confidence: 82%
“…Also, patients requiring ICU admission were significantly older than those treated on regular wards or as outpatients in the COVID-19 group but not in the seasonal influenza group. These findings suggest that age may potentially be a more important driver of disease severity for COVID-19 than for seasonal influenza 19,37 .…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…For example, although certain cytokines such as IL-6, G-CSF, IL-1RA, and MCP-1 predict death in COVID-19, their circulating levels are no different when measured in patients with other viral infections, such as influenza (Mudd et al ., 2020). However, the clinical presentation and autopsy findings of patients with COVID-19 indicate that in at least some of these patients, there may be a distinct immunological response, which is responsible for the mortality rate in excess of other viral illnesses (i.e., influenza) (Cobb et al ., 2020; Xie et al ., 2020), and results in certain coagulopathic events such as microscopic and macroscopic thrombi occurring more commonly in COVID-19 (Ackermann et al ., 2020; Bradley et al ., 2020; Carsana et al ., 2020; Fox et al ., 2020; Mei et al ., 2020). Understanding the underlying mechanisms of these relatively unique aspects of COVID-19 is crucial for targeting therapies, and, may provide insights into the pathogenesis of acute respiratory distress syndrome on a broader scale.…”
Section: Introductionmentioning
confidence: 99%